The Right to Self-Determination of Peoples through Examples of Åland Islands and Quebec : Recommendations for a Peaceful International Legal Order - Ljubović, Mirza (Review of European and Comparative Law, 2023)
In contemporary public international law, it is increasingly common that in many countries of the world and Europe, political representatives of the peoples are calling for an inalienable right to the external self-determination of the peoples involving secession to try to achieve their independence and autonomy, forming their national states to the detriment of already existing countries in which they are currently living. However, this may cause destabilization and wars in many complex multiethnic states and the European Union. Therefore, the Aland Islands and Quebec cases are extremely important for today’s understanding of the exercise of the right to self-determination of the people in contemporary public international law, in particular as the International Court of Justice in The Hague and the domestic courts invoke them as precedents to address all future cases of reference to the right of the people to external self-determination involving secession. Based on those cases, it has developed that the issue of secession is the question of the internal legal order of each sovereign country, which should deal with this issue through its constitutional legal order, and contemporary public international law should deal with its consequences. In connection with this, it is necessary to investigate and offer answers that will highlight possible abuses of the right to self-determination of all peoples as a collective human right in contemporary public international law. Such unlawful conduct may result in adverse legal consequences, in particular, the violation of basic principles of public international law, including the principles of territoriality and sovereignty of the states, the distortion of world peace and order, economic progress, the rule of law and the pursuit of basic human rights and freedoms, as well as other collective human rights, which may ultimately be the cause of provocation and lead to international and civil wars.